Focal vitreomacular traction: Resolution after ocular massage - José Javier García-Medina; Mónica del-Río-Vellosillo; Elena Rubio-Velázquez; María Dolores López-Bernal; Juan José Zafra-Pérez (American Journal of Ophthalmology Case Reports, 2019)
Purpose: Vitreomacular traction (VMT) is a relatively common ocular disorder that may distort the foveal structure causing visual symptoms. The influence of ocular massage (OM) on this condition has not been considered yet. We aim to report clinical and OCT features of VMT release associated with OM. Observations: A 70-year-old woman complained about blurred vision and metamorphopsia in her right eye for one month. Her best-corrected visual acuity (BCVA) was 20/50. Macular OCT showed focal VMT in this eye. Moderate intensity, digital OM was performed by an ophthalmologist. However, the traction was still present. The patient was instructed to perform the same OM every 8 hours at home herself. Four days later she indicated disappearance of metamorphopsia, her BCVA increased to 20/25 and OCT showed VMT release with 39-μm foveal thinning. Conclusions and importance: OM may be useful for focal VMT release. Keywords: Vitreomacular traction, Adhesion, OCT, Ocular massage, Release